Work Disruptions, Gender, and Marital Status in Gen Z Performance - Wanta Wanta; Rengga Madya Pratama; Uus M.D Fadli (CV. Creative Tugu Pena, 2026)
This study investigates how work disruptions influence the performance of Generation Z employees and whether these effects are conditioned by gender, social media use, and marital status. Drawing on the Job Demands-Resources (JD-R) framework, work disruptions are conceptualized as job demands that can undermine performance when not balanced by adequate resources. Data were collected through an online survey of 247 Gen Z employees in Indonesia using snowball sampling. Measurement instruments were adapted from Chen and Karahanna (2018) and applied with a seven-point Likert scale. Quantitative analyses tested first-order moderation (gender) and second-stage moderation (social media use and marital status). Results indicate that work disruptions significantly reduce work performance. Gender alone does not significantly moderate this relationship, and social media use also fails to act as a second-stage moderator. However, marital status strengthens the role of gender in shaping the impact of work disruptions on performance. These findings underscore the importance of integrating social factors into organizational strategies for managing Gen Z employees. Ultimately, this study contributes to both theory and practice by demonstrating that understanding the interplay of work disruptions, gender, and marital status is essential for designing effective learning and human resource development processes in the digital era.